The Risks of the use of artificial intelligence without Ethics - Fernandez Sanchez, Diego Gonzalo (2024)
The extensive research into the risks associated with unethical artificial intelligence aimed to highlight emerging problems with new technologies without proper oversight. Implementing a qualitative methodology, interviews were carried out with 10 young people from Toulouse Lautrec in Chacarilla. The results showed a growing concern about the use of digital tools, especially applications based on artificial intelligence, and revealed an alarming increase in cases of scams and false information on the internet. In conclusion, the accelerated technological evolution, including artificial intelligence, poses challenges that can exceed legal and ethical limits, generating additional concerns in crucial areas such as security, prevention of scams, protection against extortion and the urgent need to strengthen education for a informed and conscious understanding of these ever-changing challenges.